Strategi Pengembangan Bisnis Kuliner dengan Metode Swot dan Business Model Canvas di Kecamatan Purbolinggo (Studi Kasus: Bank Btpn Syariah) - Purbangga, Hafis Indra; Sutarni, Sutarni; Berliana, Dayang; Apriyani, Marlinda (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Purbolinggo District are facing internal challenges, such as limited capital, business skills, and minimal promotion, as well as external challenges, including market competition and low adaptation to technology. Bank BTPN Syariah, through the Bestee program, is providing solutions in the form of financing and business assistance, including training in financial recording, promotion strategies, and brand identity development. This study aims to analyze the costs, revenues, and incomes of culinary MSMEs, to measure income improvement after assistance, and to formulate development strategies using the SWOT and Business Model Canvas (BMC) approaches. The study is conducted using purposive sampling with seven respondents who are Bank BTPN Syariah clients engaged in culinary businesses. Data analysis consists of cost, revenue, and income calculations, as well as income differences before and after the assistance program. Furthermore, IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) analyses are used to develop the SWOT matrix. The results show that the average monthly income of culinary MSMEs is IDR 3,728,589 with an R/C ratio of 1.5 and a B/C ratio of 0.5, indicating that the business is profitable. After receiving assistance, income increases by 11.82%. Based on SWOT analysis, MSMEs are positioned in Quadrant I with a Strength–Opportunity (SO) strategy, which is to develop product and service variations, establish partnerships with fresh raw material suppliers, and build a simple distribution system. Evaluation through the BMC indicates that MSMEs have great potential to grow by determining appropriate market segments, offering value that meets consumer needs, and utilizing digital technology for wider and more effective distribution and marketing.